Bitcoin: a regulatory nightmare to a libertarian dream - Primavera De Filippi (Internet Policy Review, 2014)
This article provides an overview of national policies and current discussions on the regulation of bitcoin in Europe and beyond. After presenting the potential threat that cryptocurrencies pose to governmental and financial institutions worldwide, it discusses the regulatory challenges and the difficulty for national regulators to come up with a sound regulatory framework, which the author believes explains the current (lack of) regulatory responses in this field. The article concludes that regulation is needed, but that in order not to excessively stifle innovation in this nascent ecosystem, some of these challenges might better be addressed through self-regulation.
Keywords: 300; Cryptocurrency; Bitcoin; Digital currency